CLINICOPATHOLOGICAL CHARACTERISTICS OF PROSTATE CANCER AT THE ANATOMICAL PATHOLOGY LABORATORY OF RSUP DR. M. DJAMIL PADANG 2018–2022 - Iklil Latifah; Yenita Yenita; Ida Rahmah Burhan; Noza Hilbertina; Yevri Zulfiqar; Mutia Lailani (SINERGI : Jurnal Riset Ilmiah, 2026)
Prostate cancer is one of the most common and deadliest cancers among men, both worldwide and in Indonesia. Prostate cancer is a malignant disease characterized by abnormal cellular proliferation within the prostate tissue. Age is the most common risk factor for prostate cancer, with the risk increasing markedly in men aged 50 years and older. The most frequently identified subtype of prostate cancer is adenocarcinoma. This study was a descriptive observational study using medical record data of patients diagnosed with prostate cancer based on histopathological findings at the Anatomical Pathology Laboratory of Dr. M. Djamil General Hospital, Padang, during the period 2018–2022. Total sampling was employed. The variables analyzed included age, clinical manifestations, prostate-specific antigen (PSA) levels, histopathological cell type, and the degree of cellular differentiation of prostate cancer. The results showed that a total of 41 prostate cancer patients met the inclusion criteria. The most common age group was 55–70 years (63.4%). Local clinical manifestations were observed in 92.7% of patients, serum PSA levels >20 ng/mL in 82.9%, adenocarcinoma as the histopathological type in 100%, and poorly differentiated tumors in 82.9% of cases. The predominant histopathological type of prostate cancer was adenocarcinoma. Most patients were aged 55–70 years, commonly presented with local clinical symptoms, had serum PSA levels >20 ng/mL, and most frequently exhibited a poorly differentiated degree of tumor differentiation.